Lactobacillus rhamnosus CRL1505 nasal administration improves recovery of T-cell mediated immunity against pneumococcal infection in malnourished mice - Barbieri, Natalia Paola del Carmen (2017)
Immunobiotic lactic acid bacteria have become an interesting alternative for the prevention of respiratory infections. Previously, we demonstrated that the nasal administration of Lactobacillus rhamnosus CRL1505, during repletion of malnourished mice, resulted in diminished susceptibility to the challenge with the respiratory pathogen Streptococcus pneumoniae. Considering the known alterations induced by malnutrition on T lymphocytes and the importance of this cell population on the protection against respiratory pathogens, we aimed to study the effect of L. Rhamnosus CRL1505 nasal administration on the recovery of T cell-mediated defences against pneumococcal infection in malnourished mice under nutritional recovery. Malnourished mice received a balanced conventional diet (BCD) for seven days or BCD for seven days with nasal L. Rhamnosus CRL1505 supplementation during last two days of the treatment. After the treatments mice were infected with S. Pneumoniae. Flow cytometry studies were carried out in bone marrow, thymus, spleen and lung to study T cells, and Th1/Th2 cytokine profiles were determined in broncho-alveolar lavages and serum. The administration of CRL1505 strain to malnourished mice under recovery reduced quantitative and qualitative alterations of CD4+ T cells in the bone marrow, thymus, spleen and lung induced by malnutrition. In addition, CRL1505 treatment augmented Th2- cytokines (interleukin 10 and 4) in respiratory and systemic compartments after pneumococcal infection. These results show that modulation of CD4+ T lymphocytes induced by L. Rhamnosus CRL1505 has an important role in the beneficial effect induced by this strain on the recovery of malnourished mice. These data also indicate that nasally administered L. Rhamnosus CRL1505 may represent a non-invasive alternative to modulate and improve the T cell-mediated immunity against respiratory pathogens in immunocompromised malnourished hosts.